Vibrations in the Production System Measurement and Analysis with Water Jet Technology - Olejárová, Štefánia; Ružbarský, Juraj; Krenický, Tibor (SpringerBriefs in Applied Sciences and Technology, 2019)
This book presents the current situation in measurement and analysis of vibrations in production systems with the usage of water jet technology, focusing on sieve analysis and its principle of functioning. The authors compare the sizes of vibration accelerations amplitude with and without the usage of a narrow grain fraction. The data collection and frequency spectrum analysis presented form the basis for further research in this area. It is designed for researchers, educated public, students and university teachers with a technical focus on monitoring and diagnostics of technical equipment. .